2015
DOI: 10.1080/00207179.2015.1075175
|View full text |Cite
|
Sign up to set email alerts
|

Non-fragile reduced-order dynamic output feedbackH∞control for switched systems with average dwell-time switching

Abstract: This paper is concerned with the problem of non-fragile reduced-order dynamic output feedback H ∞ control for both continuous-and discrete-time switched systems with average dwell time switching. Lyapunov conditions for the analysis of asymptotic stability and weighted H ∞ performance are presented firstly. Then, sufficient conditions for the solvability of the problem of controller design are developed in terms of linear matrix inequalities. The design methods are suitable for general switched systems, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Due to the important role of switched systems in practice and theory, in recent years, they have been widely investigated by many researchers, for example, stability analysis with arbitrary switching and ADT switching, stability with certain switching signals, stabilization problem, and fault detection filtering . Stability and L 2 ‐gain analysis for switched systems and switched delay systems were discussed in the works of Zhang and Shi and Sun et al The nonfragile reduced‐order dynamic output feedback H ∞ control for switched systems with ADT switching was discussed in the work of Zhou et al Adaptive output feedback controller design for switched nonlinear stochastic systems with ADT was considered in the work of Niu et al The problems L 2 ‐gain analysis for switched delay systems and switched linear systems with ADT were investigated in the works of Lin et al Finite‐time stabilization and H ∞ finite‐time control for switched nonlinear systems were discussed in the works of Wang et al, Xiang and Xiao, and Zong et al, respectively. Event‐triggered finite‐time resilient control, asynchronous finite‐time filter, and event‐triggered finite‐time control for networked switched systems were discussed in the works of Ren et al Asynchronous control and asynchronous filtering for Markov switched systems were discussed in the works of Wu et al…”
Section: Introductionmentioning
confidence: 99%
“…Due to the important role of switched systems in practice and theory, in recent years, they have been widely investigated by many researchers, for example, stability analysis with arbitrary switching and ADT switching, stability with certain switching signals, stabilization problem, and fault detection filtering . Stability and L 2 ‐gain analysis for switched systems and switched delay systems were discussed in the works of Zhang and Shi and Sun et al The nonfragile reduced‐order dynamic output feedback H ∞ control for switched systems with ADT switching was discussed in the work of Zhou et al Adaptive output feedback controller design for switched nonlinear stochastic systems with ADT was considered in the work of Niu et al The problems L 2 ‐gain analysis for switched delay systems and switched linear systems with ADT were investigated in the works of Lin et al Finite‐time stabilization and H ∞ finite‐time control for switched nonlinear systems were discussed in the works of Wang et al, Xiang and Xiao, and Zong et al, respectively. Event‐triggered finite‐time resilient control, asynchronous finite‐time filter, and event‐triggered finite‐time control for networked switched systems were discussed in the works of Ren et al Asynchronous control and asynchronous filtering for Markov switched systems were discussed in the works of Wu et al…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is more significant and important to design a controller that is able to tolerate certain amount of errors in its gain value, that is, the designed controller should be resilient or nonfragile . Therefore, based on this scenario, a wealth of research results regarding nonfragile control design problems has been reported during the past few decades . Following these seminal works, research communities have employed the nonfragile control scheme to investigate the stability of large‐scale systems, see, for instance, the works of Park and Chen et al, which is of great importance in both theory and practice.…”
Section: Introductionmentioning
confidence: 99%
“…35 Therefore, based on this scenario, a wealth of research results regarding nonfragile control design problems has been reported during the past few decades. 36,37 Following these seminal works, research communities have employed the nonfragile control scheme to investigate the stability of large-scale systems, see, for instance, the works of Park 38 and Chen et al, 39 which is of great importance in both theory and practice. Notably, in the work of Chen et al, 39 the authors proposed a robust nonfragile controller for large-scale systems with randomly occurring controller failures, which can guarantee the mean-square asymptotic stability of the resulting closed-loop system.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al proposed a dynamic output feedback protocol to deal with the consensus problem [7]. The problem of non-fragile reducedorder dynamic output feedback control for both continuous and discrete-time switched systems was concerned [16]. Nevertheless, neither [8] nor [17] investigated the consensus algorithms of multi-agent network systems.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [11] and [18] hadn't taken problem into consideration. Reference [7] and [16] didn't consider the interference caused by time delays. To the best of our knowledge, there has been seldom research on using static output feedback controllers or protocols with time delays for consensus problems of multi-agent network systems.…”
Section: Introductionmentioning
confidence: 99%